UV-Ilmenite based photo-catalysis in lignin based black liquor. (March 2018) - Amriani, F; Abimanyu, H; Natsir, M; Sutrizal, L; Nursin, A
Abstract: Ilmenite can be found abundantly in iron sand from sea shore along Wolowo beach in Button district, Southeast Sulawesi, Indonesia. The ability of ilmenite in degrading lignin in black liquor has been investigated. The results of lignin degradation process in black liquor are supposed to be the potential resources for fungicide such as coniferyl, sinapyl, and p-coumaryl alcohol. The process was conducted in 10 watt ultraviolet (UV) light chamber with two parameters applying include exposure time and ilmenite composition. Two scheme of process are used by differentiating the feed, raw black liquor (scheme 1) and the liquor after adding of 1% sodium hydroxide into lignin-based sludge (scheme 2). Decolourization and lignin degradation analysis after the process were conducted by using UV-Vis spectrophotometer and LCMS, respectively. The results showed that the treatment from the scheme 1 was better than the scheme 2. Both lignin degradation and decolourization can effectively result in more than 31% by using 0.3 g ilmenite for 10 minutes UV exposure. The interim analysis by liquid chromatography-mass spectrophotometer (LCMS) exhibits the suspected target in range 309.4 to 311.39 g/mol as p-coumaryl alcohol while two other targets did not found in chromatogram. Thus, this research requires further evaluation and development to maximise the degradation result so the final goal can be achieved successfully.